Islamic Banking: Pre-requisites & Requirements to Establish Islamic Division within BankMuscat SAOG - Al-Ajmi, Wafa (2007)
Islamic banking is a new industry that has been expanding globally. Currently, there exist more than sixty banks and financial institutions that offer Shariah complaint products. A few among them are being operated under the Islamic rules and regulations. However, most of them practise in a dual system. Since Islamic finance is closely related to religion, it is different from conventional banking in many aspects. The main difference is that Islamic banks do not pay or receive interest. To satisfy the Islamic principles, Banks and financial institutions have developed new instruments satisfying the Shariah requirements and regulations. Through this study we find that the products offered by Islamic Banks are not the best solutions that capture the principles of the Shariah rules. Further, to reach the ideal financing solutions, banks need to move away from the mark-up products to equitybased solutions. With regard to the situation in Oman, political control restricts banks from offering interest-free products. Nevertheless, banks are trying to find ways to overcome this restriction.